Digital Democracy in India: E-Governance, Transparency, and the Pursuit of Good Governance - Meenu Sharma; Ananya Sharma (Yayasan Mabadi Iqtishad Al Islami, 2026)
Digital democracy and e-governance have emerged as transformative instruments for promoting transparency, accountability, and efficient public administration in India. This study examines the role of digital governance initiatives in strengthening democratic participation and reducing corruption through technology-driven governance mechanisms. Using a qualitative and doctrinal research methodology based on secondary sources, the study analyses major initiatives such as Digital India, Aadhaar, DigiLocker, BharatNet, BHIM-UPI, and MyGov. The findings demonstrate that digital governance has improved accessibility to public services, enhanced administrative efficiency, and minimized bureaucratic corruption through automation and electronic monitoring systems. Furthermore, digital platforms have expanded citizen participation in democratic processes by facilitating communication between governmental institutions and the public. However, challenges such as digital inequality, cyber-security risks, infrastructural limitations, and privacy concerns continue to affect the effectiveness of digital democracy in India